Economic Security modern transformation processes and their impact on society (case of Russia) - Tarasov, Vadim; Campbell, Jan, 1946-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The modern globalizing world is being shaped by transformational processes that permeate through all the spheres of society life. The struggle for limited resources have never been removed from the agenda of the leading economic powers. At the same time, their methods have been taking a different shape: the times of military confrontations have yielded to the era informational, geopolitical and geoeconomic wars. These phenomena determine the trends of world economy development and actualize the problem of protecting national economic interests. This study was conducted in order to analyze modern transformational processes and strategic mechanisms of providing national economic security aimed at sustainable development of society. It was shown that the processes occurring in society should be analyzed through a "civilizational prism". From that perspective culture is seen as the holding element of the informational matrix, representing a medium through which a society can be governed. The paper reconsiders the idea of economic security from conceptual viewpoint, based on reproduction approach, theory of conflicts management and modeling methods of game theory. Besides, in order to achieve compatibility of various economic security indicators, novel mathematical models were used, allowing for a comprehensive analysis. The results of applying the mathematical models in regard to the economic security of Russia demonstrated, that despite some particular positive shifts (mainly in financial sphere), the country is still facing many internal and external threats. A new Russian strategy of long-term socio-economic development is intended to improve the situation. It is aimed to solve three crucial problems, which are the creation of equal opportunities for people, encouraging innovative behavior and a considerable enhancement of economy efficiency.
Vedoucí práce: Jan Campbell
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses